Left Atrial Appendage: Physiology, Pathology, and Role as a Therapeutic Target. (7th July 2015) - Regazzoli, Damiano; Ancona, Francesco; Trevisi, Nicola; Guarracini, Fabrizio; Radinovic, Andrea; Oppizzi, Michele; Agricola, Eustachio; Marzi, Alessandra; Sora, Nicoleta Carmen; Della Bella, Paolo; Mazzone, Patrizio
Abstract : Atrial fibrillation (AF) is the most common clinically relevant cardiac arrhythmia. AF poses patients at increased risk of thromboembolism, in particular ischemic stroke. The CHADS2 and CHA2DS2-VASc scores are useful in the assessment of thromboembolic risk in nonvalvular AF and are utilized in decision-making about treatment with oral anticoagulation (OAC). However, OAC is underutilized due to poor patient compliance and contraindications, especially major bleedings. The Virchow triad synthesizes the pathogenesis of thrombogenesis in AF: endocardial dysfunction, abnormal blood stasis, and altered hemostasis. This is especially prominent in the left atrial appendage (LAA), where the low flow reaches its minimum. The LAA is the remnant of the embryonic left atrium, with a complex and variable morphology predisposing to stasis, especially during AF. In patients with nonvalvular AF, 90% of thrombi are located in the LAA. So, left atrial appendage occlusion could be an interesting and effective procedure in thromboembolism prevention in AF. After exclusion of LAA as an embolic source, the remaining risk of thromboembolism does not longer justify the use of oral anticoagulants. Various surgical and catheter-based methods have been developed to exclude the LAA. This paper reviews the physiological and pathophysiological role of the LAA and catheter-based methods of LAA exclusion.